PERBEDAAN ZONA HAMBAT PERTUMBUHAN Staphylococcus aureus PADA BERBAGAI KONSENTRASI EKSTRAK ETANOL DAUN BIDURI SECARA IN VITRO - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2018)
ABSTRACTBackground Staphylococcus aureus is a pathogenic bacteria that can cause infection. Biduri leaf has antibacterial compound such as tannin, flavonoid, saponin, and polyphenol.Objective This study aimed to know the difference of growth inhibition zone of Staphylococcus aureus at the various concentration of ethanol extract of biduri leaf and to determine an effective concentration.Methods This study was the true experiment with posttest only control design, used Kirby-Bauer disk diffusion method with five concentrations (20%, 40%, 60%, 80%,100%), positive control (chloramphenicol 30 µg) and negative control (ethanol 96%).Result The result of this study showed the average of inhibition zone diameter of each concentration consecutively 26,2 mm, 28,3 mm, 29,7 mm, 31 mm and 31,5 mm. One Way Anova statistic analysis showed that the value of p is 0.000 so there is the difference of growth inhibition zone of Staphylococcus aureus at various concentrations of ethanol extract of a biduri leaf.Conclusion The conclusion of this study is there are differences in growth inhibition zone of Staphylococcus aureus at various concentrations of ethanol extract of biduri leaf and an effective concentration that can inhibit of Staphylococcus aureus is concentration 20% with mean inhibition zone is 26,2 mm. Keywords: ethanol extract of biduri leaf; Staphylococcus aureus; inhibition zone